Prospective longitudinal comparison study of surgical therapies for peri‐implantitis: 3‐year follow‐up. (20th May 2019) - Dalago, HR; Perrotti, V; Torres de Freitas, SF; Ferreira, CF; Piattelli, A; Iaculli, F; Bianchini, MA
Abstract: Background: The aim of this study was to compare different surgical therapies to treat peri‐implantitis. Methods: Twenty‐three patients presenting one implant affected by peri‐implantitis were divided into three groups: (i) open flap debridement (OFD) and citric acid decontamination (CAD); (ii) OFD, CAD and subepithelial connective tissue graft (SCTG); (iii) OFD, CAD and implantoplasty. Modified plaque index (MPI), gingival bleeding index (GBI), keratinized mucosa (KM) width, probing depth (PD), bleeding or suppuration on probing (B/SOP), and radiographic crestal bone level were registered 1(T1), 2(T2) and 3(T3) years after treatment. Results: In Group 1 there was a significant improvement in MPI from baseline to T1, and a significant reduction in PD over time. In Group 2, none of the assessed clinical parameters showed any statistically significant variation over time. In Group 3, there was a significant decrease in PD and B/SOP over time. When comparing the 3 Groups, KM was significanlty greater in Group 2 vs. Group 1 and Group 3 at T1 and T2, and in Group 2 vs. Group 3 at T3. Conclusion: All therapies were successful in the management of peri‐implantitis; however, SCTG maintained the greatest KM width. Surgical therapies combined with mechanical and chemical decontamination contributed to peri‐implant tissue health.